Secondary actors in the origins of the Western Sahara conflict: Arab mediation efforts. - Cordero Olivero, Inmaculada; Lemus López, Encarnación (Journal of North African Studies, 2025)
In the 70s of the last century, a latent conflict was generated in Western Sahara within the Maghreb that has survived to this day and in which, since 1974, the interests of the great powers have had much to say. Some of these actors or observers have already been studied, but we still know very little about the role played by other neighbouring countries that generated dynamics of collaboration and mediation in the conflict. This work analyses the first actions undertaken by the Arab countries to try to reconcile positions and avoid an open fight. All those mediation efforts, carried out by actors with very unequal capacity for action and different motivations and internal and external interests, ended up failing. Behind them, France and the U.S., apparently neutral, promoted these meetings and talks with the aim of preventing a direct armed clash between Morocco and Algeria.